Lectures of the Nobel Week 2019 organized at Villa Nobel in Sanremo, Italy; Villa Nobel, Sanremo (Italy); December 11, 2019 - Various Authors, — (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2019)
Lectures of the Nobel Week 2019 organized at Villa Nobel in Sanremo, Italy THE NEWS OF SCIENCE FOR A SUSTAINABLE FUTURE [LE NOVITÀ DELLA SCIENZA PER UN FUTURO SOSTENIBILE] Villa Nobel • Sanremo (Italy) • December 11th, 2019 The meeting has been organized by the Alfred Nobel’s Friends International Association [Associazione Internazionale Amici di Nobel] and Centro Studi Alfred Nobel’s Friends Sanremo in collaboration with Prime Quality srl. LECT 1 • THE NEWS OF SCIENCE FOR A SUSTAINABLE FUTURE: PRESENTATION OF THE MEETING [LE NOVITÀ DELLA SCIENZA PER UN FUTURO SOSTENIBILE: PRESENTAZIONE DEL MEETING] • F. Veglio, G. Trapani (Turin and Sanremo, Italy) LECT 2 • HOW METABOLOMICS WILL CHANGE YOUR HEALTH [COME LA METABOLOMICA CAMBIERÀ LA TUA SALUTE] • V. Fanos (Cagliari, Italy) LECT 3 • NATURE OR NURTURE? WHERE INEQUALITY BEGINS? [NATURE OR NURTURE? DOVE NASCE LA DISEGUAGLIANZA?] • E. Bertino, G. Maiocco, C. Rubino, S. Deantoni, S. Sottemano, M. Turin, F. Giuliani, A. Coscia (Turin, Italy) LECT 4 • MICROBIOTA AND PERSONALIZED MEDICINE OF THE FUTURE [IL MICROBIOTA E LA MEDICINA PERSONALIZZATA DEL FUTURO] • E. Finocchiaro, A. Collo (Turin, Italy) LECT 5 • CHEMISTRY IN MEDICINE, FROM SOBRERO AND NOBEL TO THE CHALLENGES OF THE THIRD MILLENNIUM [LA CHIMICA IN MEDICINA, DA SOBRERO E NOBEL ALLE SFIDE DEL TERZO MILLENNIO] • G. Cravotto, E. Cravotto (Turin, Italy) LECT 6 • NUTRI-EPIGENOMICS: CAN WE PROGRAM HEALTH? [NUTRI-EPIGENOMICA: SI PUÒ PROGRAMMARE LA SALUTE?] • R. Gabbianelli (Camerino, Italy) LECT 7 • THE EVOLVING WORLD OF WORK: NEW STRATEGIES FOR PREVENTION AND HEALTH PROMOTION IN THE “INDUSTRY 4.0” ERA [IL MONDO DEL LAVORO CHE CAMBIA: LE NUOVE STRATEGIE PER LA PREVENZIONE E LA PROMOZIONE DELLA SALUTE NELL’INDUSTRIA 4.0] • E. Pira, E. Grillo, A. Rahmani, N. Milanesio, G. Pellecchia, R. Corgiat Loia, P. Durando (Turin and Genoa, Italy) LECT 8 • PREVENTION OF HYPERTENSION, AN INVISIBLE KILLER [PREVENZIONE DELL’IPERTENSIONE ARTERIOSA, UN KILLER INVISIBILE] • F. Veglio (Turin, Italy)